A Zwitterionic Compound with Heterocyclic Ions as Promising Heat‐Resistant Explosive. Issue 4 (5th March 2020) - Li, Chuan; Deng, Chenglong; Zhao, Baojing; Wang, Min; Zhang, Man; Zhou, Zhiming
Abstract: A unique zwitterionic compound consisting of functionalized pyrazolate and triazolium ions was synthesized and characterized fully. The zwitterionic compound, 3, 5‐dinitro‐4‐(3, 4, 5‐triamino‐4H‐1, 2, 4‐triazol‐1‐ium‐1‐yl)‐4H‐pyrazol‐4‐ide (CPTY, 3 ), exhibits superhigh heat resistance, has a decomposition temperature of 335 °C, and is insensitive to impact and friction. In addition, owing to its high density (1.82 g cm −3 ) and positive heat of formation (555.9 kJ mol −1 ), its detonation velocity and pressure are acceptable high at 8750 m s −1 and 31.5 GPa, respectively. The highly attractive physicochemical and detonation properties of 3 make it promising for use as a heat‐resistant explosive. Abstract :